2005
DOI: 10.1192/apt.11.5.338
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and physical health benefits of expressive writing

Abstract: Writing about traumatic, stressful or emotional events has been found to result in improvements in both physical and psychological health, in non-clinical and clinical populations. In the expressive writing paradigm, participants are asked to write about such events for 15–20 minutes on 3–5 occasions. Those who do so generally have significantly better physical and psychological outcomes compared with those who write about neutral topics. Here we present an overview of the expressive writing paradigm, outline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
230
0
25

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(270 citation statements)
references
References 62 publications
5
230
0
25
Order By: Relevance
“…The authors observed that the participants with more severe symptoms and co-morbid depression were less likely to comply with homework tasks. This is concerning as CBT-based approaches are not as successful without a homework component (Kazantzis & Lampropoulos, 2002) and this may be especially so for clients with a trauma history (Baikie & Wilhelm, 2005). As a consequence, even though CBT is efficacious for PTSD patients it may not be the most appropriate treatment (Scott & Stradling, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that the participants with more severe symptoms and co-morbid depression were less likely to comply with homework tasks. This is concerning as CBT-based approaches are not as successful without a homework component (Kazantzis & Lampropoulos, 2002) and this may be especially so for clients with a trauma history (Baikie & Wilhelm, 2005). As a consequence, even though CBT is efficacious for PTSD patients it may not be the most appropriate treatment (Scott & Stradling, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Baikie and Wilhelm (2005) describe the growing literature on the benefits of expressive writing over the past 20 years and conclude that overall it has been found to result in improved physical and psychological health. In this study, quotes and themes that emerged from the offenders' journals resulted in a richer description of the men's experiences following labyrinth walking.…”
Section: Discussionmentioning
confidence: 99%
“…Por un lado la facilitación de una experiencia emocional, bloqueada anteriormente, junto con la reflexión consciente del significado que se ha descubierto a través de esta experiencia (Baikie y Wilhelm, 2005;Elliott et al, 2003;Greenberg, Warwar y Malcolm, 2008;Pennebaker, 1997). Mientras que, por otro lado, permite la posibilidad de cambiar, a través del proceso de reconsolidación, los engramas de memoria anteriormente consolidados (Schiller et al, 2010;Walker et al, 2003;Xue et al, 2012).…”
Section: El Proceso Terapéuticounclassified